2023
DOI: 10.3389/fcvm.2022.1051383
|View full text |Cite
|
Sign up to set email alerts
|

A bibliometric analysis on the progress of myocardial bridge from 1980 to 2022

Abstract: IntroductionAlthough the vast majority of patients with a myocardial bridge (MB) are asymptomatic, the anomaly was found to be associated with stable or unstable angina, vasospastic angina, acute coronary syndrome, and even malignant arrhythmias and sudden cardiac death in some cases.MethodsBy retrieving the relevant literature on MB from 1 January 1980 to 31 July 2022 from the Web of Science Core Collection (WoSCC) database, we used the bibliometric tools, including CiteSpace, VOS viewer, and alluvial generat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 51 publications
0
4
0
2
Order By: Relevance
“…Few studies justified embryonic development (13,14), while others pointed to the postnatal development of MBs (15). Another theory proposed that, despite the congenital origin of the MBs, their effect is exhibited only during adulthood (23,24). The mammalian hearts were found to have subepicardial mesenchymal cells.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Few studies justified embryonic development (13,14), while others pointed to the postnatal development of MBs (15). Another theory proposed that, despite the congenital origin of the MBs, their effect is exhibited only during adulthood (23,24). The mammalian hearts were found to have subepicardial mesenchymal cells.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies have reported inconclusive impact of MBs (2, 5, 16,17,22,23), cardiac rhythm abnormalities like depression of QTc and monomorphic ventricular tachycardia were reported in children with hypertrophic cardiomyopathy with MBs (11). Direct compression of the coronary artery or the alteration of the distribution of atheroma by the MBs were the reasons for the strong association between MBs and coronary heart disease in young as well as old adults (33).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Normalmente, a PM tem sua ocorrência na artéria coronária descendente anterior, com profundidade entre 1mm a 10mm e comprimento aproximado de 10mm a 30mm. A porção íntima do segmento tunelizado se apresenta mais fina do que o segmento proximal, além de conter predominantemente células musculares lisas do subtipo contrátil (CHEN L, et al, 2023;ZHANG M, et al, 2023).…”
Section: Fisiopatologia Da Ponte Miocárdicaunclassified
“…With regard to the current status of research and the trajectory of specific research areas, there are many studies that use bibliometrics and knowledge mapping. [65][66][67][68] CiteSpace and the alluvial generator, which were used in this study, are the 2 of the most bibliometric tools. Our analysis strategy is similar to those employed in previous research.…”
Section: Pcsk9 Inhibitormentioning
confidence: 99%